Assessing employment and labour market effects of rural infrastructure investments in the Sahel region: Cases of Niger and Côte d'Ivoire - Alkassoum Saadatou Sangare; Béké Tite Ehuitché; Mahamadou Tankari (University of Bonn, Center for Development Research (ZEF), 2024)
Investments in infrastructure are necessary to achieve the objective of Sustainable Development Goal2 (SDG2), which is to "end hunger, ensure food security and promote sustainable agriculture" and to also create jobs in the Sahel region, specifically in Niger and Côte d'Ivoire. A significant portion of the populations of these two countries live in rural areas where they are mainly employed in agriculture. But due to a low availability of of infrastructure, many rural populations do not benefit from basic services such as access to energy and irrigation. Starting from an input-output analysis and a multiplier model based on the social accounting matrices of Niger and Côte d'Ivoire, this research analyzes the impact of an investment policy in rural infrastructure on job creation and agricultural development. The results confirm the significant contribution of development of rural infrastructure for employment and highlight the importance of adjusting investments to local circumstances for maximizing the employment contribution. In the case of Niger where the initial state of the coverage of water and electricity needs is very low, additional investments in such infrastructures make it possible to maximize job creation. In Côte d'Ivoire, employment creation appears greater following investments in road infrastructure. However, these jobs do not include long-term cumulative effects that would result from the increase in income. A large part of the jobs created are in the construction sector. The other additional jobs would come from sectors of agriculture, trade, and food processing to which are added the extractive industry for the case of Niger and the basic metal industries and transport in the case of Côte d'Ivoire. The study recommends that Sahelian countries align their investment strategy in infrastructure with a skills development strategy in the field of construction. This contributes to the structural transformation of Sahelian economies and increases the field of possibility for unqualified rural workers.
Keywords: O18; Q10; R15; Q16; 330; Rural Infrastructure; Agricultural development; Employment; Input output model